Reduction of reproductive parameters of Pogonias courbina (Perciformes, Sciaenidae) in southern Brazil - dos Santos, Paulo R.S. [UNESP]; Velasco, Gonzalo (Elsevier, 2021)
In southern Brazil, the Southern Black Drum Pogonias courbina is an estuarine-dependent fish, endangered due to intense fishing in the past decades. This study calculated the reproductive parameters, age (A50) and length of first maturation (L50), batch fecundity, total fecundity and extension of the reproductive period of the P. courbina, in order to test the hypothesis of reduction, caused by heavy exploitation. The value for A50, calculated for both sexes, was 2.13 years. The L50 values for males and females were 42.5 and 46.4 cm respectively, while batch and total fecundity were 63,300 and 2,532,000 oocytes, in a reproductive period that extends from late October to March. Except for the extension of the reproductive period, it was observed that there was a reduction of all the reproductive parameters when compared with specimens, caught before overfishing. The data indicate that management strategies aimed at ecological and fishery sustainability are urgent and necessary.
Keywords: Fecundity; First sexual maturity; Overfishing; Pogonias courbina; Southern black drum